(Re)pensando a gestão do estágio não-obrigatório em arquivologia na Universidade Estadual da Paraíba: impasses e perspectivas - Benevides, Alyne Gisele Fernandes da Silva (2021)
This research aims to analyze the non-mandatory internship management in the Archival Science Course and the given perspectives for its upgrading. This is an applied research of qualitative approach, conducted at the Archival Science Course of the State University of Paraíba (UEPB), which had the year of 2019 as its time frame. About its objectives, it is classified as descriptive and exploratory, structured from a bibliographic and document research which provides theoretical subsidy about internship. Regarding document research, we analyzed the national legislation about non-mandatory internship, object of the Law no. 11,788/2008 (Lei de Estágio — Internship Law), as well as the UEPB and the Archival Science Course internal rules, institutional management activities reports, and data provided from the Internship Coordination of the Archival Science Course (CECA). From the systematization of the Internship Law procedures, we propose a design of the internship management and how it might be carried out according to the UEPB and the Archival Science Course regulations. Subsequently, we address the issue in the empirical field, throughout the conduction of semi structured interviews among the subjects involved with the internship management in the Coordination of Internship and Academic Programs (CEPA) and in the Archival Science Course. We analyzed the data through the Bardin’s Content Analysis Technique. The results showed the complex structural weakness of the Non-Obligatory Internship Program management at UEPB, being presented questions and suggestions aiming to contribute to this management (re)thinking inside UEPB with the participation of the Archival Science Course academic community. The contributions presented were systematized in the following axes: Program; Regulations; Granting Parties; Coordination; Monitoring and Evaluation; Professors and Students.